Active learning in head and neck trauma: outcomes after an innovative educational course. Issue 1 (January 2022) - Milne, S.; Walshaw, E.G.; Webster, A.; Mannion, C.J.
Abstract: Excellence in teaching and learning is fundamental to the provision of quality training for doctors and for this a sound knowledge of the principles of adult learning theory is important. We present an educational course in head and neck trauma skills for emergency medicine (EM) registrars, using the pedagogical principle of active learning. Our aim was to provide trainees with skills in the evaluation and management of hard and soft tissue injuries to the head, neck, and mouth. Active learning has been shown to provide a superior experience in classrooms, creating a 'deep' understanding of the material. To maximise learning, we used these principles to develop small group seminars led by a diverse range of teachers that allowed trainees to acquire hands-on skills. Questionnaires that were completed before and after the course showed an appreciable educational impact. We conclude that innovative teaching methods facilitate the sharing of knowledge that will benefit patient care.